Exploiting user grouping and energy harvesting in downlink cellular system - Minh-Sang Van Nguyen; Phuc Huu Dang; Nhan Duc Nguyen (Bulletin of Electrical Engineering and Informatics, 2022)
A mobile communication system combining energy harvesting with a cooperative nonorthogonal multiple access (NOMA) system is presented in this research. In the proposed scheme, the relay is assumed to have a limited power source, and it will harvest radio energy from the base station (BS) to serve the near and far users. In this scenario, we consider two possible situations during information transmission in the NOMA application system: perfect successive interference cancellation (SIC) and imperfect successive interference cancellation. The system performance is assessed primarily based on closed-form outage probability expressions. Numerical simulations are conducted to examine the outage probability of the proposed scheme and to verify the derived formulas. The study results have proved that the system performance is still good under the imperfect SIC condition, and several optimal parameters to improve the system performance have been found. Moreover, our research results have shown the superior performance of the proposed model compared with current orthogonal multiple access (OMA) networks.